Causal relationships between rheumatism and dyslipidemia: A two-sample Mendelian randomization study - Zhang, Guangyang; Cai, Yuanqing; Liang, Jialin; Zhang, Jianan; Jing, Zhaopu; Lv, Leifeng; Zhang, Rupeng; Song, Jidong; Dang, Xiaoqian; Song, Qichun (Frontiers in Endocrinology, 2022)
Background Dyslipidemia is often observed in rheumatic diseases, such as ankylosing spondylitis (AS), rheumatoid arthritis (RA), and systemic lupus erythematosus (SLE), yet it remains to be detected whether rheumatic diseases have a causal effect on dyslipidemia. Methods Significant (P < 5 × 10-8) and independent (r2 < 0.1) single-nucleotide polymorphisms in genome-wide association studies were selected as instrumental variables to conduct Mendelian randomization (MR) analysis. Inverse variance weighted, weighted median, and MR–Egger regression were adopted for the causal inference. Subsequently, sensitivity analysis was conducted to assess the stability and reliability of MR. Results The MR results revealed positive causal relationships of AS with total cholesterol (TC) (β = 0.089, 95% CI = 0.050 to 0.128, P = 6.07 × 10-6), low-density lipoprotein (LDL) (β = 0.087, 95% CI = 0.047 to 0.127, P = 1.91 × 10-5), and high-density lipoprotein (HDL) (β = 0.043, 95% CI = 0.001 to 0.074, P = 0.009). There was no causal effect of RA on TC (β = 0.008, 95% CI = 4.86 × 10-4 to 0.017, P = 0.064), LDL (β = 6.4 × 10-4, 95% CI = -0.008 to 0.007, P = 0.871), or HDL (β = 0.005, 95% CI = -0.003 to 0.013, P = 0.200). Additionally, SLE had negative causal links for TC (β = -0.025, 95% CI = -0.036 to -0.015, P = 4.42 × 10-6), LDL (β = -0.015, 95% CI = -0.025 to -0.005, P = 0.003), and HDL (β = -0.013, 95% CI = -0.021 to -0.004, P = 0.004). The results were stable and reliable. Conclusion This study suggested positive causal effects of AS on TC, LDL, and HDL and negative causal effects of SLE on these cholesterol levels, which could provide much help for the pathogenesis and treatment of rheumatic disease patients with dyslipidemia.